Genetic Comparison of H3N2 Influenza Virus in Indonesia with WHO Recommended Strains During the Period 2004 – 2021 - Johny Hartawan Sutrisno; Triyana Sari; Sari Mariyati Dewi Nataprawira; Erick Sidarta (Syntax Idea)
Influenza caused by A/H3N2 virus is one commonly found infections in tropical countries. Vaccination policy against A/H3N2 virus is already established for Northern and Southern hemisphere, however, no specified policy is established for tropical countries such as Indonesia. World Health Organization (WHO) has recommended Indonesia to use vaccine formulation designated for Northern hemisphere. Some studies, however, have shown that there were mismatches between recommended vaccine and circulating strains present in Asian countries, which might have caused regional outbreaks. This study was aimed to compare the genetic makeup of WHO recommended vaccine strain with H3N2 virus circulating in Indonesia. A total of 147 HA and 148 NA complete nucleotide sequences from Indonesian population, as well as 14 HA and 14 NA WHO-recommended nucleotide sequences, were downloaded from GISAID. These sequences were subjected to phylogenetic analysis using MEGA 11. Furthermore, antigenicity of these isolates was analyzed using Kolaskar and Tangonkar Prediction method accessible through IEDB website and Vaxijen 2.0. This study revealed that WHO-recommended vaccine strain for southern hemisphere in 2010 were compatible with Indonesian strains circulating in 2009. Furthermore, there were no recommended vaccine strain that matched strain in circulation between 2010 to 2012 and 2019. Kolaskar and Tongaonkar antigenicity prediction analysis had simulated that several mutations rendered some antigenic epitopes of HA and NA protein to be non-antigenic. These findings highlighted the importance of reliable national surveillance network of influenza to prevent regional epidemic and the development of local influenza vaccine to better accommodate Indonesian population.